Legitimacy Washing in Sustainable Finance: A Critical Literature Review Legitimacy and Conceptual Framework - Listya Putri, Imamatin; Budi Sulistiyo, Agung; Wulandari Widiyanti, Novi (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
As ESG disclosure becomes an institutional norm in sustainable finance, concerns are rising about the symbolic use of sustainability narratives to project legitimacy without corresponding ethical or operational change. While legitimacy theory has been widely applied to explain organizational responses to social expectations, it has rarely been used to interrogate the potential manipulation of legitimacy itself. This conceptual paper introduces and theorizes the notion of legitimacy washing—defined as the strategic deployment of ESG disclosures and symbolic sustainability practices to secure perceived legitimacy in the absence of substantive transformation. Through a critical literature review, the paper synthesizes existing scholarship on ESG disclosure, greenwashing, and legitimacy theory, identifying key gaps in how symbolic compliance is understood and assessed. It then develops a conceptual framework that outlines the drivers, mechanisms, and types of legitimacy washing, distinguishing it from related concepts such as greenwashing and CSR decoupling. The paper contributes to theory by expanding the boundaries of legitimacy theory; to practice by offering diagnostic indicators for symbolic ESG disclosure; and to policy by proposing regulatory responses to mitigate performative sustainability. The framework offers a foundation for future empirical research on how legitimacy is constructed, contested, and potentially compromised in the evolving landscape of sustainable finance.